Improving the 2D drawing soft skills of Banten Province vocational high school teachers and laboratory assistants through workshops and training - Syarif Abdullah; Ni Ketut Caturwati; Dhimas Satria; Dwinanto Dwinanto; Sidik Susilo; Haryadi Haryadi; Hadi Wahyudi; Mekro Permana Pinem; Dedy Triawan Suprayogi (Journal of Community Service in Science and Engineering (JoCSE), 2023)
A community service program in the form of workshops and soft skills training in the form of 2D drawing skills for teachers and laboratory assistants at Vocational High Schools (SMK) in Banten Province has been implemented. This activity is in partnership with SMK YP Fatahillah 1 Cilegon. This program is implemented to improve the ability of educators to help students face the world of work and industry after they graduate. The application used in this workshop and training is the AutoCAD application. The training material is about an introduction to AutoCAD, drawing simple 2D objects and complex 2D objects. Participants in this training activity consisted of teachers and laboratory assistants. This training activity uses presentation methods, tutorials, practice, discussions, questions and answers, and exercises. The training results showed increased participants' soft skills in 2D drawing using the AutoCAD application. Program pengabdian kepada masyarakat dalam bentuk workshop dan pelatihan softskill berupa keterampilan menggambar 2D pada guru dan laboran di Sekolah Menengah Kejuruan (SMK) di Provinsi Banten telah dilaksanakan. Kegiatan ini bermitra dengan SMK YP Fatahillah 1 Cilegon. Program ini dilaksanakan untuk meningkatkan kemampuan para pendidik untuk membantu peserta didik dalam menghadapi dunia kerja dan industri setelah mereka lulus. Aplikasi yang digunakan pada workshop dan pelatihan ini yaitu dengan menggunakan aplikasi AutoCAD. Materi pelatihan yang diberikan yaitu tentang pengantar AutoCAD, menggambar objek 2D sederhana dan menggambar objek 2D kompleks. Peserta kegiatan pelatihan ini terdiri dari guru dan laboran. Pelaksanaan kegiatan pelatihan ini dilakukan dengan metode presentasi, tutorial, praktik, diskusi, tanya jawab, dan latihan. Hasil pelatihan didapatkan peningkatan kemampuan softskill para peserta dalam drawing-2D dengan menggunakan aplikasi AutoCAD.